Validation of PleaseApp: a digital tool for the assessment of receptive pragmatic abilities in children with neurodevelopmental disorders - Andrés-Roqueta, Clara; Flores-Buils, Raquel; Igualada, Alfonso (Frontiers in Psychiatry, 2024)
Background: Pragmatic skills allow children to use language for social purposes, that is, to communicate and interact with people. Most children with neurodevelopmental disorders (NDD) face pragmatic difficulties during development. Nevertheless, pragmatic skills are often only partially assessed, because the existing instruments usually focus on specific aspects of pragmatics, and are not always adapted to children with communication difficulties. In this sense, digital tools (e.g., apps) are an optimal method to compensate for some of these difficulties. Moreover, there is a lack of pragmatic tools measuring the receptive domain. Therefore, the present study aims to validate PleaseApp as a digital instrument that measures eight pragmatic skills, by presenting the design of the assessment tool and its psychometric properties. Method: PleaseApp was designed based on previous empirical studies of developmental pragmatics in children with and without NDD. PleaseApp assesses eight receptive pragmatic skills: figurative language, narrative, reference, indirect speech acts, visual and verbal humor, gesture-speech integration, politeness, and complex intentionality. The study involved 150 typically developing children between 5 and 12 years of age. Results: A confirmatory factor analysis proposes an eight-factor model with no underlying factor structure. The eight tests that compose PleaseApp have obtained a model with a good fit, and with adequate reliability and validity indices. Discussion: PleaseApp is an objective, valid and reliable tool for assessing pragmatic skills in children with NDD. In this sense, it helps to assess whether a child has acquired pragmatic skills correctly according to his/her age, and also to clarify the specific problems a child has in eight different components in order to plan personal and personalised interventions.